Maturation processes and structures of small secreted peptides in plants - Tabata, Ryo; Sawa, Shinichiro (Frontiers in Plant Science, 2014)
In the past decade, small secreted peptides have proven to be essential for various aspects of plant growth and development, including the maintenance of certain stem cell populations. Most small secreted peptides identified in plants to date are recognised by membrane-localized receptor kinases, the largest family of receptor proteins in the plant genome. This peptide-receptor interaction is essential for initiating intracellular signalling cascades. Small secreted peptides often undergo post-translational modifications and proteolytic processing to generate the mature peptides. Recent studies suggest that, in contrast to the situation in mammals, the proteolytic processing of plant peptides involves a number of complex steps. Furthermore, NMR-based structural analysis demonstrated that post-translational modifications induce the conformational changes needed for full activity. In this mini review, we summarise recent advances in our understanding of how small secreted peptides are modified and processed into biologically active peptides and describe the mature structures of small secreted peptides in plants.